The impact of friends, family members and subjective norm on intention to purchase halal personal care products: the moderating role of spiritual intelligence / Sulaiman Nawawi … [et al.] - Nawawi, Sulaiman; Hassan, Faridah Haji; Mustaffa, Abaidullah; Mohammad Hamzah, Iskandar; Basir Malan, Irfah Najihah (Academy of Contemporary Islamic Studies (ACIS), 2018)
The purpose of this paper is to validate the impact of friends’ influence, family members’ influence and subjective norms on one’s intention to purchase halal personal care products. It also aims to investigate the moderating role of spiritual intelligence on the relationship between subjective norms and purchase intention. Data from 405 Muslim respondents in Klang Valley, Malaysia were collected using a combination of purposive and quota sampling techniques. The data were later analysed using the Statistical Package for Social Sciences (SPSS) – Version 21 and Partial Least Square–Structural Equation Modelling (PLS-SEM) – Smart PLS 3. The results revealed that friends and family members’ influences were significant antecedents of subjective norm. It was also found that one’s intentions to purchase halal personal care products were significantly and positively influenced by subjective norm. As expected, the positive relationship between subjective norm and intention to purchase the products was found to have been moderated by spiritual intelligence. This paper empirically justifies the impact of friends’ influence, family members’ influence and subjective norm on purchase intention in the context of halal personal care products. Additionally, this study further validates the moderating role of spiritual intelligence on the relationship between subjective norm and purchase intention.